THE INFLUENCE OF SUPPLIER RELATIONSHIP MANAGEMENT ON COMPETITIVE ADVANTAGE THROUGH SUPPLY CHAIN INTEGRATION - Ruth Srininta Tarigan (Petra Christian University, 2026)
This study aims to analyze the effect of Supplier Relationship Management on Competitive Advantage, with Supply Chain Integration as a mediating variable, in medium- and large-scale manufacturing companies in East Java. The study uses an explanatory research approach with a non-probability sampling method through judgment sampling. Data were obtained by distributing questionnaires to 97 respondents and measured using a five-point Likert scale. Data analysis was performed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with the help of SmartPLS software. The results show that Supplier Relationship Management has a positive and significant effect on Supply Chain Integration (β = 0.766; p < 0.001) and Competitive Advantage (β = 0.286; p = 0.034). Supply Chain Integration also has a positive and significant effect on Competitive Advantage (β = 0.341; p = 0.021). Furthermore, the indirect effect of Supplier Relationship Management on Competitive Advantage through Supply Chain Integration was positive and significant (β = 0.261; p = 0.027). These findings indicate that Supply Chain Integration acts as a partial mediator in the relationship between Supplier Relationship Management and Competitive Advantage. Therefore, effective supplier relationship management needs to be supported by information integration, coordination, and involvement among supply chain actors so that companies can improve flexibility, delivery accuracy, the ability to meet customer needs, and competitive position.